Pengendalian Persediaan Bio Solar dan Pertalite Pada SPBU Nelayan 58.611.01 yang Dikelola PT. Gresik Migas - Firdaus, Achmad Zuhaeri; Handayani, Anita; Alkusani, Alkusani (Universitas Muhammadiyah Gresik, 2024)
Background – The ever-evolving era of globalization, accompanied by the continuous improvement of telecommunication network services worldwide, including in Indonesia, has driven telecommunication companies to compete for profits. The growth of the telecommunication sector, further supported by the Covid-19 pandemic, sets it apart from other sectors, which generally experienced declines under the same conditions. Objective – To determine the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), and Total Assets Turnover on Return on Assets (ROA). Design / Methodology / Approach – This study was conducted on telecommunication sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period, with a research sample of 10 companies. The sampling method used was purposive sampling. The data analysis technique applied was multiple linear regression. Findings – The partial test shows that the Current Ratio (CR) variable does not have a significant effect on the Return on Assets (ROA) variable. Meanwhile, the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) variables significantly influence the Return on Assets (ROA) variable. Simultaneous testing results indicate that the CR, DER, and TATO variables collectively affect ROA. Research Implication – Reevaluating financial ratio values that are deemed unsatisfactory to facilitate assessment and improvement while maintaining or even enhancing the company's performance is crucial to achieving favorable financial ratios in terms of liquidity, solvency, activity, and profitability. This ensures that investors and creditors feel confident in investing or lending their capital to the company. Limitations – The test results show that 27.8% of the variation in the Return on Assets (ROA) variable can be explained. Since some variables were found to have no significant effect, it is recommended to consider the potential influence of other variables, such as inventory turnover, cash turnover, accounts receivable turnover, working capital, and others.